An actuator with tuneable resonant frequency for active vibration damping. (July 2023) - Hendijanizadeh, Mehdi; Sharkh, Suleiman; Mosca, Pietro; Daley, Steve
This paper explores implementing active resonance frequency tuning of adaptive tuned vibration absorbers (ATVA) by coupling a vibration absorber comprising a voice coil actuator (VCA) and a sprung inertial mass to a solenoid actuator (SA). In this device, the DC current flowing through the SA generates negative magnetic stiffness and varies the equilibrium position of the nonlinear spring of the VCA, thus changing the effective stiffness of the system and its resonant frequency. The paper details the analytical design steps and the parametric sizing process of designing the SA to maximize its force density within defined magnetic, dimensions and thermal constraints. The design of the SA was verified using finite element analysis (FEA), manufactured and coupled to a VCA to make the complete ATVA system. The experimental results demonstrate the tunability of the resonance frequency of the ATVA by controlling the SA's DC current. It is shown that the system's resonance frequency can be shifted by up to 23% of the fundamental resonance frequency, which improves the effectiveness of the ATVA at damping a broader range of excitation frequencies.